Multi-criteria decision analysis of timber–concrete composite floor systems in multi-storey wooden buildings. Issue 3 (3rd July 2021) - Movaffaghi, Hamid; Yitmen, Ibrahim
ABSTRACT: This study aims to present a multi-criteria decision analysis (MCDA) for comprehensive performance evaluation of the alternative design of timber–concrete composite (TCC) floor system. Considered objectives are serviceability and sustainability performance with associated criterion as (1) comfort class regarding springiness and vibrations, (2) architectural quality with associated criterion as open spaces, (3) environmental aspect with associated criterion as CO2 emissions and (4) cost aspect with associated criterion as the total costs. Analytical Hierarchy Process (AHP) and Complex Proportional Assessment (COPRAS) as the methods in the multi-criteria analysis have been combined for (1) determining the weighting of criteria based on the survey results, (2) verifying the consistency ratio of decision matrix made by experts and (3) for ranking and selecting the optimal concept design among design candidates. According to the results, the TCC floor with the span length of 7.3 m belonging to comfort class A has got the highest ranking. However, sensitivity analysis indicates that the TCC floor with a 9.0 m span length belonging to comfort class A shall be selected as the optimal concept design. The study contributes by developing a complete concept design tool for TCC floor systems using AHP combined COPRAS methods to handle both beneficial and non-beneficial criteria.